2013
DOI: 10.1002/dmrr.2393
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant use and new‐onset diabetes: a systematic review and meta‐analysis

Abstract: Summary Antidepressant use has been linked to new-onset diabetes. However, the existing literature on this relationship has yielded inconsistent findings. The primary objective of this study was to systematically synthesize the literature on the relationship between antidepressant use and new-onset diabetes using meta-analysis. A systematic literature search was conducted to identify relevant studies in seven electronic databases. Two independent reviewers identified the final list of studies to be included in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 43 publications
3
43
0
2
Order By: Relevance
“…The association between antidepressant use and incident diabetes mellitus (DM) remains inconclusive [62]. Some reports point to a higher risk of DM [63,64,65] whereas others do not [66,67]; however, a recent systematic review and meta-analysis found that antidepressants (mainly SSRIs and TCAs) increase the risk of DM (OR = 1.5, 95% CI 1.08-2.10; HR = 1.19, 95% CI 1.08-1.32) [68]. As the included studies were observational, this association may not be causal [69].…”
Section: Weight Gain and Metabolic Disturbancesmentioning
confidence: 99%
“…The association between antidepressant use and incident diabetes mellitus (DM) remains inconclusive [62]. Some reports point to a higher risk of DM [63,64,65] whereas others do not [66,67]; however, a recent systematic review and meta-analysis found that antidepressants (mainly SSRIs and TCAs) increase the risk of DM (OR = 1.5, 95% CI 1.08-2.10; HR = 1.19, 95% CI 1.08-1.32) [68]. As the included studies were observational, this association may not be causal [69].…”
Section: Weight Gain and Metabolic Disturbancesmentioning
confidence: 99%
“…[74][75][76] A meta-analysis, though included only observational studies, reported increase in diabetes onset likelihood (OR 51.50, 95% CI 1.08-2.10, HR 51.19, 95% CI: 1.08-1.32). 77 However, most studies 78,79 provide evidence for elevated diabetes risk with the concurrent use of tricyclic antidepressants and selective serotonin reuptake inhibitors (SSRIs) (OR=1.89), 80 the long-term use of both tricyclic antidepressants (incidence rate ratio, IRR=1.77) and SSRIs (IRR=2.06) in at least moderate daily doses, 81 as well as the use of antidepressants medication in high-risk patients. 82 Further, amitriptyline, imipramide and mirtazapine are associated substantially with weight gain, nortriptyline and paroxetine appear to have intermediate effect, whereas bupropion and fluoxetine are linked with weight loss.…”
Section: Medication Schizophrenia and Type 2 Diabetesmentioning
confidence: 99%
“…Antidepressants have been reported to affect glycaemic control and to trigger the onset of type 2 DM [115][116][117][118][119]. It is difficult to differentiate between the possible diabetogenic side effects of antidepressants per se (such as weight gain), from the effects associated with the depressive disorder [116,119]. SSRIs have been reported to confer a glucose lowering effect [117,120] and animal model studies have reported glucose increment from TCAs [121].…”
Section: Antidepressants In Elderly Patientsmentioning
confidence: 99%
“…Treatment decisions are therefore often based on data from younger adults [112]. Antidepressants have been reported to affect glycaemic control and to trigger the onset of type 2 DM [115][116][117][118][119]. It is difficult to differentiate between the possible diabetogenic side effects of antidepressants per se (such as weight gain), from the effects associated with the depressive disorder [116,119].…”
Section: Antidepressants In Elderly Patientsmentioning
confidence: 99%